2004
DOI: 10.3141/1863-09
|View full text |Cite
|
Sign up to set email alerts
|

Development and Implementation of a Continuous Vertical Track-Support Testing Technique

Abstract: As part of an Association of American Railroads (AAR) research program, the Transportation Technology Center, Inc., a subsidiary of AAR, has developed a new method using its track loading vehicle (TLV) technique to measure vertical track deflections under given vertical loads while in motion. The technique was developed to identify weak track locations and to measure the load-carrying capacity of existing tracks to aid and prioritize track maintenance and to improve railroad operational performance. Discussed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 1 publication
0
9
0
2
Order By: Relevance
“…Over the past two decades, two deflection/track modulus measurement techniques have been developed and tested in North America: the Track Loading Vehicle (TLV) developed by the Transportation Technology Center, Inc. (TTCI) and the University of Nebraska Real-Time Vertical Track Deflection Measurement System (UNL system, commercially known as MRail) developed under the sponsorship of the Federal Railroad Administration (FRA). 6,13,[17][18][19] The focus of this study is on the UNL system that has shown the potential to measure deflection at relatively higher speeds and at lower equipment costs. 20 The UNL system measures the relative vertical distance (referred to as Y rel ) between the rail surface and the rail/wheel contact plane at a distance of 1.22 m from the nearest wheel to the sensor system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past two decades, two deflection/track modulus measurement techniques have been developed and tested in North America: the Track Loading Vehicle (TLV) developed by the Transportation Technology Center, Inc. (TTCI) and the University of Nebraska Real-Time Vertical Track Deflection Measurement System (UNL system, commercially known as MRail) developed under the sponsorship of the Federal Railroad Administration (FRA). 6,13,[17][18][19] The focus of this study is on the UNL system that has shown the potential to measure deflection at relatively higher speeds and at lower equipment costs. 20 The UNL system measures the relative vertical distance (referred to as Y rel ) between the rail surface and the rail/wheel contact plane at a distance of 1.22 m from the nearest wheel to the sensor system.…”
Section: Introductionmentioning
confidence: 99%
“…The application of on-train techniques for measuring the track modulus at revenue speed provides a comprehensive overview of railway line conditions over long distances of track. 12–16 Despite this significant advantage, measuring the vertical rail deflection from a moving car is a challenge due to the difficulty in defining a reference point. Moreover, the interpretation of the on-train deflection measurement data still needs more investigation.…”
Section: Introductionmentioning
confidence: 99%
“…A number of train-mounted measurement systems have been developed for the estimation of track stiffness continuously along rails. 16–25 This includes the Track Loading Vehicle (TLV; developed by the Transportation Technology Center, Inc.) and the University of Nebraska Real-Time Vertical Track Deflection Measurement System (commercially known as MRail; developed under the sponsorship of the Federal Railroad Administration) that measure the VTD from moving railcars under axle loads that are representative of fully loaded railcars. 16,17,19,20 These train-mounted VTD measurement systems have potential use for the estimation of maximum bending moments and stresses in the rail by applying the mathematical correlation between rail deflections and bending stresses.…”
Section: Train-mounted Vtd Measurement Systemsmentioning
confidence: 99%
“…Train-mounted instruments that measure the vertical track deflection (VTD) under train loading have become available over the last decade. 16–20 These instruments present an opportunity to estimate rail bending stresses over long distances, and thus characterize the spatial variation of bending stresses. 15,16 However, the effect of track modulus and its variability on the mathematical correlation between rail deflection and bending stresses has not been thoroughly investigated and, as a result, the method used to estimate rail bending stresses from VTD measurements is overly simplistic.…”
Section: Introductionmentioning
confidence: 99%
“…Although these techniques provide accurate estimations of track stiffness, they are laborious and time-consuming, especially when multi-point measurements are required. On the other hand, on-train measurement systems allow the measurement of rail deflections over long distances and thus provide a good overall evaluation of the entire railway network [10][11][12][13][14][15]. Comprehensive analysis is typically needed to investigate the relationship between deflection measurements from on-train systems and track modulus [16,17].…”
Section: Introductionmentioning
confidence: 99%